Safety message broadcast in vehicular networks - Bi, Yuanguo, 1980-; Zhou, Haibo; Zhuang, Weihua; Zhao, Hai (Of Dongbei da xue (1993)) (Springer, 2017)
"This book presents the current research on safety message dissemination in vehicular networks, covering medium access control and relay selection for multi-hop safety message broadcast. Along with an overall overview of the architecture, characteristics, and applications of vehicular networks, the authors discuss the challenging issues in the research on performance improvement for safety applications, and provide a comprehensive review of the research literature. A cross layer broadcast protocol is included to support efficient safety message broadcast by jointly considering geographical location, physical-layer channel condition, and moving velocity of vehicles in the highway scenario. To further support multi-hop safety message broadcast in a complex road layout, the authors propose an urban multi-hop broadcast protocol that utilizes a novel forwarding node selection scheme. Additionally, a busy tone based medium access control scheme is designed to provide strict priority to safety applications in vehicle-to-infrastructure communications. This book offers useful insights into protocol design and inspires a new line of thinking in performance improvements for safety applications in vehicular networks. It is a valuable resource for professionals, researchers, or advanced-level students working in vehicular networks or quality of service"--Provided by publisher.
Keywords: Vehicular ad hoc networks (Computer networks); elektronické knihy; electronic books